Perancangan Desain User Interface/User Experience Web Layanan Informasi Kamus Dengan Metode Lean User Experience (Lean UX) Pada Universitas Pamulang - Eryana Wahyu; Sofa Sofiana (BULLET : Jurnal Multidisiplin Ilmu, 2022)
With the development of applications, either via the web or mobile, applications cannot be separated from human-computer interactions. The ease of using the application is the target of developers to attract users. It can not be separated from the user interface and user experience. In the area of education, the delivery of information also uses the same technology as popular technology. It also triggers the same problems as applications in general. the difficulty in understanding and operating the application is the main problem experienced by users in using the application. Using the lean user experience (lean ux) method with a four-stage loop process, declare assumptions, create an MVP, run experiments, feedback and research. Development using this method prioritizes user opinions so that applications can be developed in accordance with what users want. In this research, experimental testing involving several application users. With about 30 users involved in research, users will do a little test whose results will be accumulated. From this research, the influence of users on application development becomes one of the factors whether the application is suitable for use or needs to be repaired. By experimenting and designing on an ongoing basis it will produce the expected application.